Determination of bisphenol A and bisphenol S by a covalent organic framework electrochemical sensor. (August 2020) - Pang, Yue-Hong; Huang, Yu-Ying; Wang, Li; Shen, Xiao-Fang; Wang, Yi-Ying
Abstract: Bisphenol A (BPA) is a widely produced chemical that is mainly used as raw material for manufacturing plastic products. It is an endocrine disruptor and causes irreversible damage to the human body. Bisphenol S (BPS), an alternative to BPA, has low dose effects on toxicology and genotoxicity. Herein, we constructed a highly porous crystalline covalent organic framework (COF, CTpPa-2)-modified glassy carbon electrode (GCE) for the electrochemical sensing of BPA and BPS. The electrochemical properties of the CTpPa-2/GCE were characterized using galvanostatic charge-discharge, cyclic voltammetry and differential pulse voltammetry. The CTpPa-2/GCE exhibited remarkable electrocatalytic activity, and the electrochemical responses for BPA and BPS were found to be linear in the concentration ranges of 0.1–50 μM and 0.5–50 μM with detection limits of 0.02 μM and 0.09 μM (S/N = 3), respectively. Moreover, the fabricated sensor was utilized to determine BPA and BPS in bottle samples with recoveries of 87.0%–92.2% and migration rates of 13.2%–28.0%. Graphical abstract: An electrochemical sensing platform based on COF CTpPa-2 has been developed for the determination of BPA and BPS in bottle samples and for the determination of their migration rates. Image 1 Highlights: The covalent organic framework improves the electrocatalytic performance. An electrochemical sensor for bisphenol A and bisphenol S was developed. The sensor has potential applications in environmental analysis and food safety. Abstract : An electrochemical sensing platform based on COF CTpPa-2 has been constructed for the determination of BPA and BPS in bottle samples and for the determination of their migration rates.